Enhancing creative thinking and cultural literacy: project-based learning with field trip support - Syarif, Erman; Tabbu, Muhammad Ansarullah S.; Jamaluddin, Asham Bin; Saputro, Alief (Institute of Advanced Engineering and Science, 2024)
One of the main challenges in learning cultural geography is to develop a deep understanding of cultural diversity and creative ability in analyzing and describing the relationship between humans and their environment. This study investigates the effect of the field trip-based project-based learning (PjBL) learning model on students’ creative thinking ability and cultural literacy in a Cultural Geography course. The research design used is a comparative experimental design in three different groups. The subjects in this study were students majoring in Geography at Universitas Negeri Makassar (UNM) in the 3rd (odd) semester of the 2023/2024 academic year. The research sample was selected purposively (purpose sampling) based on the same academic ability characteristics of the population. The collected data will be analyzed using the ANACOVA test statistical method. The results showed that the 2-tailed significance level (Sig.) was 0.000, far below the generally accepted alpha level (α=0.05) which indicated a significant difference in the use of the PjBL model, the PjBL-field trip (PjBL-FT) model, and the conventional learning model in improving creativity and cultural literacy skills. The considerable difference in the mean post-test scores underscores the effectiveness of field trip-based project-based learning (PjBL-FT) in improving creative skills. The results imply that this model can be used to create innovative learning so that it can make a good contribution to learning.